Increased Mortality from Extrapancreatic Infections in Hospitalized Patients with Acute Pancreatitis - Guido Grajales-Figueroa; Héctor Adrián Díaz Hernández; Martín Alejandro Chacón Portillo; Luis F. Uscanga; Mario Peláez-Luna; Jorge Hernández Calleros (Gastroenterology Research and Practice)
Nosocomial extrapancreatic infections in patients with acute pancreatitis (AP) are associated with a higher mortality even after adjusting the risk for the severity of the pancreatitis. The aim of this study was to describe the clinical features of hospitalized patients with AP who died during their hospitalization and to evaluate risk factors associated with mortality. We performed a descriptive study of the clinical features of adult patients who died from AP during their hospitalization and a case control study with a paired group of patients that survived AP during a 10-year period. Data of interest were collected from the medical records and are presented with appropriate measures of central tendency and dispersion. For the case control study, the primary outcome evaluated was death, and to evaluate associated clinical features and determine differences between groups, we performed the χ2 or Fisher’s exact tests for categorical variables and the Student t-test or Mann-Whitney U test for continuous variables as appropriate. We found 48 patients with acute pancreatitis who died within the period of the study during hospitalization; from these, 50% were men, mean age was 53.2 years, and the most common etiology was biliary obstruction by gallstones in 45.8%. The global mortality rate was of 2.5%. A total of 43.7% patients had infected pancreatic necrosis, and in 58.3%, some extrapancreatic infection was documented, being the most common urinary tract infection in 50%, bacteremia in 50% and pneumonia in 33.3%. Clinical features associated with mortality were the presence of organ failure (p<0.001), nosocomial complications (p<0.001), infected necrosis (p<0.001), and extrapancreatic infections (p=0.002). From the different extrapancreatic infections, only bacteremia (p=0.001) and pneumonia (p=0.011) were associated with higher mortality. In conclusion, extrapancreatic infections are associated with increased mortality among hospitalized patients with acute pancreatitis, in particular, bacteremia and pneumonia with an isolated pathogen.